Preventable Death Rate of Trauma Patients in a Non-Regional Trauma Center - Kwanhoon Park; Wooram Choi; Sungho Lee; Kang Yoon Lee; Dongbeen Choi; Han-Gil Yoon; Ji Young Jang (Journal of Acute Care Surgery, 2023)
Purpose A nationwide study (2012–2017) of preventable trauma death rates (PTDR) showed a 15.3% decrease after Regional Trauma centers were initiated. However, in non-trauma centers with an Emergency Department there is limited data of preventable mortality in trauma patients. Therefore, the purpose of this retrospective study was to investigate preventable mortality in trauma patients in a non-regional trauma center and determine the effect of initiating a Trauma Team. Methods There were 46 deaths of trauma patients recorded in the National Health Insurance service Ilsan Hospital (NHISIH) in South Korea from January 2019 to December 2021. These patients’ preventable deaths were analyzed by an expert panel review considering the implementation of the Trauma Team in April 2020. Results All deaths were attributable to blunt trauma with an average Injury Severity Score of 26.0 ± 19.2, Revised Trauma Score of 5.05 ± 3.20 and Trauma and Injury Score of 56.6 ± 41.3. The most frequent cause of death was traumatic brain injury followed by respiratory arrest. The most frequent error was delayed transfusion followed by delayed treatment of bleeding. Treatment errors occurred the most in the Emergency Room followed by the Intensive Care Unit. The PTDR of patients before the involvement of a Trauma Team (January 2019 to March 2020) and after the Trauma Team was initiated in April 2020 decreased from 27.27% to 4.27%, respectively (p = 0.021). Conclusion The introduction of a dedicated Trauma Team in a non-regional trauma center significantly reduced the overall PTDR in trauma patients.